Financial Distress of Multi-Finance Companies in Emerging Markets - Satriadi, Dharma; Siregar, Hermanto; Manurung, Adler Haymans; Zulbainarni, Nimmi (International Journal of Social Science and Business, 2024)
Financial distress is when the company cannot pay what has been agreed upon when it is due. This paper discusses financial difficulties in multi-finance companies from 2010 to 2023. Forecasting financial difficulties uses the Merton Model method, adapted from the Black-Scholes Model for option prices. The method used to predict financial difficulties for multi-finance companies uses the Merton Method, as described previously, which is an adaptation of the Black-Scholes method. His research found that multi-finance companies still have negative interest margins. Increasing the credit disbursed also needs to receive attention from company management. The company's marketing costs also appear minor and can be imitated by other institutions. The probability of financial distress for multi-finance companies is very high and cannot be separated from the business characteristics of multi-finance companies. Multifinance companies still have negative interest margins. Increasing the credit disbursed also needs to receive attention from company management; the company's marketing costs also appear minor and can be imitated by other institutions; the probability of financial distress for multi-finance companies is very high and cannot be separated from the business characteristics of multi-finance companies.